KERJASAMA INDONESIA DAN PERSERIKATAN BANGSA-BANGSA (PBB) DALAM UPAYA PENURUNAN TINGKAT PREVALENSI STUNTING DI INDONESIA MELALUI GERAKAN SCALING UP NUTRITION (SUN) PERIODE 2013 - 2021 - Muhammad Fariz Nugroho, (2022)
One of the health problems currently being fought globally is stunting. Stunting is caused by a lack of nutrition obtained by a child since in the womb results in stunted physical characteristics. Not only physical problems, stunting can also result in a decrease in a person's cognitive level which will have an impact on the quality of a country's human resources and ultimately on the country's economic level. In 2010, the Scaling Up Nutrition (SUN) Movement was presented by the United Nations as an effort to reduce the global stunting prevalence rate. This was welcomed by Indonesia, which finally joined the movement in 2011. Over time, efforts to reduce the prevalence of stunting in Indonesia have brought many changes and improvements, as evidenced by the trend of decreasing stunting rates since Indonesia was incorporated into the SUN Movement. This study seeks to explain efforts to reduce the prevalence of stunting, especially in Indonesia through the Scaling Up Nutrition Movement (SUN Movement) using the Global Governance Theory with its derivative concept, namely the Global-Public Private Partnership which has proven to produce results in the mirror of the stunting prevalence rate which has a declining trend from 2013- 2021. However, with a target of 14% in 2024, it seems that Indonesia still has a lot of work to do to achieve this target. This research is expected to be able to analyze, explain, and provide input so that efforts to reduce the prevalence of stunting can be carried out in a substantive, holistic, and targeted manner.